2009
DOI: 10.1590/s1415-47572009005000017
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal location of 18S and 5S rDNA sites in Triportheus fish species (Characiformes, Characidae)

Abstract: The location of 18S and 5S rDNA sites was determined in eight species and populations of the fish genus Triportheus by using fluorescent in situ hybridization (FISH). The males and females of all species had 2n = 52 chromosomes and a ZZ/ZW sex chromosome system. A single 18S rDNA site that was roughly equivalent to an Ag-NOR was detected on the short arms of a submetacentric pair in nearly all species, and up to two additional sites were also observed in some species. In addition, another 18S rDNA cluster was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
2
23
0
1
Order By: Relevance
“…The Z chromosomes have additional heterochromatin in one or both telomeric regions, depending on the species, whereas the W chromosomes were almost entirely heterochromatic, except for the p arms in all species (Figure 1), in agreement with previous studies (Artoni and Bertollo, 2002;Diniz et al, 2009;Yano et al, 2014). The two-color FISH with 18S and 5S rDNA showed that both sites are colocalized on the p arms of the chromosome pair 3 in T. signatus, with an 18S rDNA additional site adjacent to the Wq telomere (Figure 2).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The Z chromosomes have additional heterochromatin in one or both telomeric regions, depending on the species, whereas the W chromosomes were almost entirely heterochromatic, except for the p arms in all species (Figure 1), in agreement with previous studies (Artoni and Bertollo, 2002;Diniz et al, 2009;Yano et al, 2014). The two-color FISH with 18S and 5S rDNA showed that both sites are colocalized on the p arms of the chromosome pair 3 in T. signatus, with an 18S rDNA additional site adjacent to the Wq telomere (Figure 2).…”
Section: Resultssupporting
confidence: 92%
“…In fact, both techniques were critical to demonstrate the sequences that are still shared by both sex chromosomes or, otherwise, that those are more exclusive to one of them. Noteworthy, it was evidenced that the end of the Wq has a high concentration of female-specific sequences (Figures 2-4), where an 18S rDNA cluster is also located in all Triportheus species so far analyzed (Artoni and Evolution of sex chromosomes in congeneric species CF Yano et al Bertollo, 2002;Nirchio et al, 2007;Diniz et al, 2009;Marquioni et al, 2013;Yano et al, 2014). Sex chromosomes carrying 18S rDNA sequences have already been reported in several other vertebrates, such as Characidium fishes (Scacchetti et al, 2015), cane toad Bufo marinus (Abramyan et al, 2009), Chinese softshell turtle Pelodiscus sinensis (Kawai et al, 2007) and tiger snake Notechis scutatus (O'Meally et al, 2010).…”
Section: Chromosomal Rearrangements and Sex Chromosome Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence of colocalization of 5S and 18S rDNA has been reported for some species of Acipenseriformes (Fontana et al, 2003), Salmoniformes (e.g., Pendas et al, 1994;Moran et al, 1996;Fujiwara et al, 1998;Rossi & Gornung, 2005), Cypriniformes (Inafuku et al, 2000), Characiformes (e.g., Almeida-Toledo et al, 2002;Cioffi et al, 2009;Diniz et al, 2009 and references therein), Perciformes (Nirchio et al, 2009;Pisano & Ghigliotti, 2009) and, now also, Mugiliformes (present study). Interestingly, all the possible syntenic conditions have been found, either the two sets of genes in distinct and disjoint chromosomal regions, as in Astyanax scabripinnis (Mantovani et al, 2005) and Parodon tortuosus (=Parodon nasus) (Vicente et al, 2001), or in adjacent regions, as in M. incilis (present study) and Triportheus nematurus (Diniz et al, 2009), or the 5S rRNA genes interspersed along the clusters of 45S rDNA, as in Notothenioidei (Pisano & Ghigliotti, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Mechanisms such as conversion and unequal crossing-over often occur within these gene arrangements during evolution, according to Dover (1986). In this context, according to Diniz et al (2009), the location of 5S and 18S rDNA sites on different chromosomes and different positions would be a way to restrict the setting of unfavorable rearrangements, for example, translocation of segments between these genes. Under the phylogenetics systematics light, this characterization may place the status of this character as an apomorphy, which is yet to be proven regarding other species from the genus, for example, Pimelodus fur has not exhibited this synteny (Garcia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%